Da Messias kom til København: Om Messias-receptionen i København gennem to århundreder - Topp, Morten (Danish Yearbook of Musicology, 2005)
When Messiah Came to Copenhagen Two Centuries of Messiah Reception in Copenhagen After Handel’s death in 1759 the knowledge of Messiah spread surprisingly slow on the continent, presumably because few outside the U.K. were able to sing in English. A German translation by F.G. Klopstock and C.D. Ebeling was used for the first time in 1775 at a performance conducted by C.F.E. Bach in Hamburg. The translation formed the basis for Mozart’s arrangement of Handel’s instrumentation and for most of the performances in Germanspeaking areas well into the twentieth century. That the music society, ‘Det harmoniske Selskab’, in Copenhagen wished to perform Messiah in 1786 might have been due to the rumours of the great Handel performances in London in 1784 and 1785. Since neither a suitable choir nor qualified soloists were available, the parts were sung by a solo quartet thus contributing to the complete failure, which is apparent from Peter Grønland’s review of the event. Hence this particular performance strengthened the general reluctance to perform Baroque music — a reluctance that had prevailed since J.A. Scheibe’s arrival in Copenhagen in 1740. For many years the Baroque choral works disappeared completely from the concert repertoire. Apart from the very modest extract of the work performed by N.W. Gade in ‘Musikforeningen’ (mainly nos. 12-15, 34a and 39), a more extensive extract of Messiah was not seen again in Copenhagen until 1877, when the conductor Frederik Rung led ‘Cæciliaforeningen’ in a successful performance in German at Christiansborg Slotskirke. However, in a contemporary review there were still traces of the sceptical attitude towards Baroque music expressed so strongly by Grønland 91 years earlier. Up to 1933 ‘Cæciliaforeningen’ had performed the work nine times after which Danish National Radio took over and until 1994 the work was performed 11 times, mostly in a reduced version and in the early years often sung in Danish. The first complete performance of Messiah, however, took place in 1954 with Mogens Wöldike and Københavns Drengekor. The fact that Messiah has become a Christmas tradition is due to the music society, ‘Akademisk Orkester og Kor’ (AOK), who has performed the work in Københavns Domkirke every year since 1946 with 1951 as the only exception. Over the years the audiences were of a moderate size but from 1975 the numbers increased, and in the 1990s AOK gave 3-4 annual, full house performances. Many Copenhagen choirs supported the Messiah tradition, which meant that around 25 performances of Handel’s work could be heard at Christmas shortly before the millennium. Almost half of these were full-length performances, thus emphasizing that text and music form a whole.